A descriptive study on the use of a gonadotropin releasing hormone agonist ovulation trigger in assisted reproductive techniques - Unterslak, Yosef Yitchok (My University, 2015)
The risk of developing ovarian hyperstimulation syndrome post-induction of ovulation in patients undergoing in-vitro fertilisation has been greatly reduced by the introduction of gonadotropin-releasing hormone agonists for ovulation induction. The pregnancy outcomes have not been fully evaluated and specifically not when fresh embryo transfer takes place on day three or day five of the medicated cycle as opposed to frozen embryo transfer in a fresh non-medicated cycle.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Obstetrics and Gynaecology University of the Witwatersrand 2014